Dielectric properties of lead zirconate titanate/Au composite film prepared by aerosol deposition - Dong, Xue; Lee, Bom; Ghulam, Asghar; Akedo, Jun; Yu, Hak Ki; Choi, Jae Young; Park, Jae Hyuk (Materials Chemistry and Physics, 2022)
A lead zirconate titanate (PZT)/Au composite film was prepared using aerosol deposition (AD) to modulate the dielectric properties of PZT. X-ray diffraction and transmission electron microscopy analyses confirmed that the crystallinity of the PZT/Au (Au wt %: 0–0.2) composite polycrystalline film deposited at room temperature was controlled throughout the heat treatment process. The degree of dispersion of Au nanoparticles was confirmed through analysis of the plasmonic absorption wavelength (∼620 nm) of nanoparticles occurring in the refractive index 2.4–2.5 region of PZT matrix. The dielectric constant of the film increased to more than three times that of pure PZT as the wt % of Au nanoparticles increased. In addition, because the Au nanoparticles were well dispersed throughout the PZT matrix, the dielectric loss was very low. We expect AD to be widely used for the future development of dielectric complexes because this method enabled the straightforward fabrication of a thin composite film.
Keywords: Aerosol deposition; Au nanoparticle; Cristallinity; Dielectrics property; Lead zirconate titanate; Lead zirconate-titanate; matrix; Polycrystalline film; X- ray diffractions; Zirconate titanate; Dielectric properties; Films; Nanocomposites; PZT